Trouble in paradise [videorecording (DVD)] - Jones, Grover, 1893-1940; Harling, W. Franke (William Franke), 1887-1958 (Criterion collection, 2003)
"When thief Gaston Monescu meets his true love in pickpocket Lily, they embark on a scam to rob lovely perfume company executive Mariette Colet. But when Gaston becomes romantically entangled with Mme. Colet, their larcenous ruse is jeopardized and Gaston is forced to choose between two beautiful women"--Container